Improving Village Community Skills with Local Corn Food Creations in Giriwoyo, Wonogiri Regency: MENINGKATKAN KETERAMPILAN MASYARAKAT DESA DENGAN KREASI BAHAN PANGAN LOKAL JAGUNG DI GIRIWOYO KABUPATEN WONOGIRI - Sumarmi, Sumarmi; Triyono, Kharis; Karyantina, Merkuria; Handayani, Dewi; Rosariastuti, MMA Retno (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
This community servis aims to improve the skills of the people of Giriwoyo village, Wonogiri, through training in the creation of local corn food. The methods used include practical training and demonstrations on making various processed corn-based products, such as cakes and snacks. Apart from that, this activity also succeeded in creating awareness of the potential of corn as a food source with economic value. It is hoped that participants can utilize the skills acquired to develop small businesses, increase income, and contribute to the welfare of local communities.